PENERAPAN STANDAR OPERASIONAL PROSEDUR TERHADAP PELAYANAN PRIMA SERVICE ASSISTANT (SA) DI BANK JATIM SYARIAH KC MALANG - Muhammad Faris Nafi’udin; Mohammad Nabil Alfi; Muhammad Iqbal Fathoni; Naufal Alwan Athallah (Institut Agama Islam Negeri Kerinci, 2023)
In the banking world, Service Assistant (SA) has a significant role in serving needs, satisfying customers, and maintaining good customer relations. A service Assistant (SA) is required to provide excellent service at the main gate. To be able to provide excellent service, an officer must be essential services related to knowledge of bank products and be able to apply applicable Standard Operating Procedures (SOPs). This study aims to determine how Standard Operational Procedures (SOP) are applied in the Service Assistant (SA) section to provide excellent service at Bank Jatim Syariah KC Malang. This study uses a qualitative descriptive method; researchers try to describe a symptom, event, and event during the study. The object of this study researchers took the subject matter of the research as a case study, namely the Application of Standard Operating Procedures to Prima Service Assistant (SA) Services at Bank Jatim Syariah KC Malang. The results showed that the application of SOPs in the excellent service of Service Assistants must be able to play an active role in serving customers internally and externally. To provide excellent service according to SOPs, such as in terms of appearance, body gestures, intonation, clear and comfortable explanations, and provide smiles by treating and to all customers, such as priority customers from the bank.